Tuning the internal structures of CdSeS nanoparticles by using different selenium and sulphur precursors - Chen, X; Hutchison, J; Dobson, P; Wakefield, G (2010)
Alloyed CdSeS nanoparticles (NPs) with composition gradient and homogeneous internal structures have been successfully prepared in aqueous solution by using different selenium and sulphur precursors. The as-prepared NPs form a homogeneous internal structure when sodium selenide and sodium sulphide were used as selenium and sulphur precursors, respectively. Gradient internal structures were obtained for alloyed CdSeS NPs prepared by using sodium selenosulphate and sodium thiosulphate as selenium and sulphur precursors, respectively. The method takes advantage of the fact that different selenium/sulphur sources release selenium/sulphur ions at different rates or have different reaction rates of selenium/sulphur toward cadmium. © 2009 Elsevier B.V. All rights reserved.